Sarcopenia trajectories and associated factors after lung transplantation: a growth mixture model study - Mengshan Xie; Fei Zeng; Fangfang Hao; Peipei Gu; Jiangshuyuan Liang; Yandie Wang (Frontiers in Medicine, 2026)
Background Sarcopenia is common after lung transplantation and is associated with poor outcomes, yet its postoperative course is dynamic and may differ between recipients. We aimed to identify latent classes of sarcopenia trajectories during the first year after lung transplantation and the factors associated with them. Methods In this retrospective cohort study, 264 recipients who underwent lung transplantation at a tertiary hospital between June 2023 and March 2025 were assessed with the Ishii score at up to six time points (preoperatively and at 1 week and 1, 3, 6, and 12 months). Growth mixture modeling identified latent trajectory classes, missing data were handled with full information maximum likelihood, and multinomial logistic regression identified associated factors. Results The Ishii score followed an inverted V-shaped course, with the prevalence of probable sarcopenia rising from 55.7% preoperatively to 95.6% at 1 week and declining to 28.4% at 12 months. Three Ishii score trajectories were identified: low-risk (40.5%), moderate-risk (36.7%), and high-risk (22.7%). Older age (OR 1.08), lower preoperative BMI (OR 0.81), lower preoperative FEV1%pred (OR 0.97), longer ICU stay (OR 1.11), and a higher NRS 2002 score (OR 1.39) were independently associated with the high-risk trajectory (all p < 0.05). Recipients in the high-risk trajectory also had the poorest physical function at one year. Conclusion Postoperative Ishii score trajectories were markedly heterogeneous among lung transplant recipients. Repeated Ishii screening with trajectory-based, individualized management may support the early identification and targeted care of high-risk recipients.